2022
DOI: 10.3390/diagnostics13010055
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Microvascular Damage and Internal Organ Involvement in Scleroderma: Focus on Lung Damage and Endothelial Dysfunction

Abstract: Background. Systemic sclerosis (SSc) is an incurable connective tissue disease characterized by decreased peripheral blood perfusion due to microvascular damage and skin thickening/hardening. The microcirculation deficit is typically secondary to structural vessel damage, which can be assessed morphologically and functionally in a variety of ways, exploiting different technologies. Objective. This paper focuses on reviewing new studies regarding the correlation between microvascular damage, endothelial dysfunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 101 publications
(277 reference statements)
1
14
0
1
Order By: Relevance
“…Systemic sclerosis (SSc) is a rare connective tissue disorder characterized by diffuse microangiopathy and immune dysregulation, pathogenic elements that ultimately lead to the most known feature of this disease, namely tissue fibrosis of skin and internal organs [ 1 , 2 ]. Skin thickening is one of the most evident and studied aspects of SSc since it can be easily analyzed and mostly because it has been widely demonstrated that a more extensive skin involvement correlates with more severe internal organ damage, poor prognosis and increased disability [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Systemic sclerosis (SSc) is a rare connective tissue disorder characterized by diffuse microangiopathy and immune dysregulation, pathogenic elements that ultimately lead to the most known feature of this disease, namely tissue fibrosis of skin and internal organs [ 1 , 2 ]. Skin thickening is one of the most evident and studied aspects of SSc since it can be easily analyzed and mostly because it has been widely demonstrated that a more extensive skin involvement correlates with more severe internal organ damage, poor prognosis and increased disability [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…decreased blood flow) has been proved by many studies [ [6] , [7] , [8] , [9] , [10] ]. Nailfold papilloscopy (NVC) is a non-invasive, reliable, inexpensive, reusable and running-in method for determining structural microvascular injury in SSc [ 11 ]. Laser speckle contrast analysis (LASCA) is a new safety technology to quantify blood perfusion (BP) in different body regions of patients with SSc and healthy control group.…”
Section: Introductionmentioning
confidence: 99%
“…ANA might not only represent biomarkers of disease but also play a pathogenic role through immune-mediated mechanisms and molecular mimicry. ANA (particularly anti-topoisomerase-I and anti-RNA polymerase III antibodies) appear to be transported within the cell by direct interaction with intercellular components and receptors, targeting intracellular topoisomerase and RNA polymerase by the corresponding antibodies [22,23,[49][50][51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…Supporting this evidence is the response of some SSc patients to B-cell-targeted therapies and the role of activated B cells in the success of allogeneic bone marrow transplantation for the treatment of SSc [24,25,[55][56][57][58][59][60]. In addition, SSc patients have macro-and microvascular damage and impaired peripheral blood perfusion [6,[48][49][50][51][52][53]. Nail fold video capillaroscopy (NVC) plays an important role because it is a noninvasive and reliable method to detect microvascular involvement.…”
Section: Introductionmentioning
confidence: 99%